Sudden Stop: When Did Firms Anticipate the Potential Consequences of Covid-19? - Lukas Buchheim; Carla Krolage; Sebastian Link (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Covid-19 hit firms by surprise. In a high frequency, representative panel of German firms, the business outlook declined and business uncertainty increased only when the spread of the Covid-19 pandemic led to domestic policy changes: The announcement of nation-wide school closures on March 13 caused by far the largest change in business perceptions. In contrast, business perceptions hardly reacted to any other potential source of information: Firms did not learn from foreign policy measures, even if they relied on inputs from China or Italy. The local, county-level spread of Covid-19 cases affected expectations and uncertainty, albeit to a much lesser extent than the domestic policy changes.
Keywords: E66; E32; H32; D22; D84; 330; expectations; uncertainty; policy; Covid-19; firms